An exploratory qualitative assessment of factors influencing childhood vaccine providers' intention to recommend immunization in the Netherlands - Mollema Liesbeth; Staal Jojet M; van Steenbergen Jim E; Paulussen Theo GWM; de Melker Hester E (BMC, 2012)
Abstract Background Under the Dutch national immunization program (NIP), childhood vaccination is not mandatory, but its recommendation by childhood vaccine providers (CVP) is important for maintaining high vaccination coverage. We therefore examined factors related to providers' intentions to recommend vaccinations to parents of young children. Methods We conducted four focus group discussions with nurses and physicians who provide vaccines to children 0-4 years old in diverse regions of the Netherlands. Three groups represented CVPs at child welfare centers (CWCs) serving the general population, with the fourth representing anthroposophical CWCs. Elements of the Theory of Planned Behaviour (TPB) were used to design the groups; thematic analysis was used to structure and analyze the dataset. Results Four main themes emerged, including 1) perceived responsibility: to promote vaccines and discuss pros and cons with parents (although this was usually not done if parents readily accepted the vaccination); 2) attitudes toward the NIP: mainly positive, but doubts as to NIP plans to vaccinate against diseases with a low perceived burden; 3) organizational factors: limited time and information can hamper discussions with parents; 4) relationship with parents: crucial and based mainly on communication to establish trust. Compared to CVPs at standard CWCs, the anthroposophical CWCs spent more time communicating and were more willing to adapt the NIP to individual cases. Conclusions Our qualitative assessment provides an overview of beliefs associated with providers' intention to recommend vaccinations. They were motivated to support the NIP, but their intentions to recommend vaccinations were affected by the perceived relevance of the vaccines, practical issues like limited time and by certain types of resistant parents. These results will inform future studies to test the magnitude and relative impact of these factors.